THE SOCIAL AND FAMILY INTERACTION OF ADOLESCENT WITH PORNEOGRAPHY ADDICTION IN THE BORNEO MADANI FOUNDATION OF SAMARINDA, INDONESIA - Rosdiana Rosdiana; Godefridus Bali Geroda (Jurnal Kesehatan, 2021)
During their development, adolescents experience emotional, cognitive, and psychological changes. One of the changes that cannot be avoided is motivation and high curiosity about various things that happen to them, including problems related to sexuality. The availability of sophisticated technology makes it easy to access pornographic content so that many teenagers enjoy and become addicted. Lifestyle, lack of supervision, lack of good communication, too high demands, violence against children, not knowing the potential of children and discrimination from parents and the environment can trigger adolescents to be exposed to pornography.This research is used qualitative research methodology with a case study approach through in-depth interviews, observation, and documentation to 15 informants. The objective of this research is to determine the impact of the social and family environment due to pornography addiction.The results showed that, the impact on the social environment, increasing adolescent sexual exploration so that free sex and risky sexual behavior can occur, changing attitudes and perceptions about sexuality that women and children are sex objects only, easily lie with anyone because they do not care about price self and self-concept, it's easy to hurt others to channel their passions. The impact on the family environment, the difficulty in concentrating in the learning process and carrying out daily activities that require attention, so that parents are often reprimanded and even scolded by parents at home because the rooms are dirty and messy and lack of attention or indifference to problems in the family, are not sensitive on the interaction among family members so that there is no warmth, love, and care for each other in family members.